Deciphering nature’s secrets: the antibacterial power and phytochemical characterization of six medicinal fern species - Rapheal Wangalwa; Perfect Nasasira; Clement Olusoji Ajayi; Bruhan Kaggwa; Eunice Olet; Casim Umba Tolo; Gerald Eilu; Grace Rugunda-Kagoro (My University, 2025)
Plants have been key in the development of novel antimicrobial agents and other drugs. However, studies on empirical evidence of the antimicrobial properties of plants have largely focused on higher plants while neglecting lower vascular plants, including ferns. This study investigated the antibacterial potency and characterized the phytochemical profile of six fern species originating from Bwindi Impenetrable National Park, Uganda. The antibacterial potency of the extracts was assessed against pathogenic bacteria using the microtiter plate and agar well diffusion assays. Key generic phytochemicals were quantified through Ultra-Violet (UV)-vis spectrophotometric techniques. Fingerprinting of the extraction components was attained using High Performance Liquid Chromatography (HPLC)-based methods. The fern species contain bioactive compounds such as phenolics and saponins, with species such as Dicranopteris linearis giving high yields of such compounds 158.01±0.95 Gallic Acid Equivalent (GAE) mg/g and (479.40±1.07 DE mg/g) of extract, respectively. Fern extracts demonstrated substantial antimicrobial activity against common pathogenic bacteria such as K. pneumonia, E. coli, P. aeruginosa, and S. aureus with Minimum Inhibitory Concentrations (MICs) as low as 0.39% w/v and Minimum Bactericidal Concentrations (MBCs) as low as 3.13 w/v for some fern species such as Oleandra distenta, Asplenium friesiorum, Dicranopteris linearis, and Marattia fraxinea. The ethanolic extract of Marattia fraxinea was potent against P. aeruginosa with the highest zones of inhibition of 32.67±0.58mm at 50% w/v concentration while D. linearis and O. distenta aqueous extracts were potent against the gram-positive bacteria with the highest zones of inhibition of 27.7±1.15 and 26.67±1.53 mm, respectively, at 50% w/v concentration. This study has elucidated that extracts of fern species can be effective against common pathogenic bacteria.
Keywords: ferns; phytochemical profile; antibacterial activity; pathogenic bacteria